2018
DOI: 10.1039/c8cy00950c
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic removal of 1,2-dichloroethane over LaSrMnCoO6/H-ZSM-5 composite: insights into synergistic effect and pollutant-destruction mechanism

Abstract: The synergy between LaSrMnCoO6 and H-ZSM-5 in the catalytic destruction of 1,2-dichloroethane based on the dechlorination and dehydrochlorination processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 59 publications
1
27
0
Order By: Relevance
“…1,2-dichloroethane (1,2-DCE) is one of the most important chlorinated VOCs emitted in industrial flue gases, [801][802][803] since it is used as an intermediate in the production of polyvinyl chloride. Additional uses are as a solvent in metal degreasing and paint removers, a starting material for paint, and a dispersant for plastics and elastomers.…”
Section: 2-dichloroethanementioning
confidence: 99%
“…1,2-dichloroethane (1,2-DCE) is one of the most important chlorinated VOCs emitted in industrial flue gases, [801][802][803] since it is used as an intermediate in the production of polyvinyl chloride. Additional uses are as a solvent in metal degreasing and paint removers, a starting material for paint, and a dispersant for plastics and elastomers.…”
Section: 2-dichloroethanementioning
confidence: 99%
“…In recent years, zeolites with abundant acid solid [2,14,15,16] such as H-MOR, H-ZSM5, H-BETA, have received more attention, due to the abundant BrØnsted and Lewis acid selected to improve the adsorption and oxidation performance, and resistance to Cl poisoning. Weng et al [17] indicated that the Mn0.8Ce0.2O2 showed deactivation attributed to the accumulation of chloride or coke on the surface of Mn-Ce mixed oxides.…”
Section: Introductionmentioning
confidence: 99%
“…Hosseini 17 reported that LaMnO 3 /ZSM‐5 has a higher activity for 2‐propanol conversion than 1% Pt/Al 2 O 3 . Tian et al 18 synthesized a composite of LaSrMnCoO 6 /HZSM‐5 by hydrothermal method and found that HZSM‐5 improved the activity of perovskite catalyst. Compared with other zeolites like NaY, MOR, and Beta, ZSM‐5 has more acid sites and higher reducibility, which are beneficial for the supports of efficient catalysts 15 .…”
Section: Introductionmentioning
confidence: 99%